Real-time Sound Localization Using Generalized Cross Correlation Based on 0.13 mu m CMOS Process - Jin, Jungdong; Jin, Seunghun; Lee, SangJun; Kim, Hyung Soon; Choi, Jong Suk; Kim, Munsang; Jeon, Jae Wook (IEEK PUBLICATION CENTER, 2014)
In this paper, we present the design and implementation of real-time sound localization based on 0.13 mu m CMOS process. Time delay of arrival (TDOA) estimation was used to obtain the direction of the sound signal. The sound localization chip consists of four modules: data buffering, short-term energy calculation, cross correlation, and azimuth calculation. Our chip achieved real-time processing speed with full range (360 degrees) using three microphones. Additionally, we developed a dedicated sound localization circuit (DSLC) system for measuring the accuracy of the sound localization chip. The DSLC system revealed that our chip gave reasonably accurate results in an experiment that was carried out in a noisy and reverberant environment. In addition, the performance of our chip was compared with those of other chip designs.